The Influence of Entrepreneurship Courses on Students' Entrepreneurial Interests - Muhamad Stiadi (Jurnal Mantik, 2021)
This study aims to determine the effect of entrepreneurship courses on students' interest in entrepreneurship and aims to determine how much influence this variable has. The method used in this research is descriptive quantitative with testing using SPSS. The data in this study were obtained using an online questionnaire using google form and respondents' answers in the study using a likert scale. The results of this study indicate that the calculated F value is 14,234 with a significant 0,000, while ? = 0.05 because the P value is smaller than ? = 0.05, which means that the entrepreneurship subject variable which includes the material and method of delivering lectures has a positive and significant effect on' interest in students entrepreneurship. early childhood education at Ivet University. The magnitude of the influence of the entrepreneurship subject variable on students' interest in entrepreneurship is 44.2%.